IMPLEMENTATION OF REGULATION OF THE MINISTER OF SOSIAL OF THE REPUBLIC INDONESIA NUMBER 1 IN 2018 ON PROGRAM KELUARGA HARAPAN IN GAMBIRANOM VILAGE BATURETNO DISTRICT WONOGIRI REGENCY (Study Article 7 Letter b Beneficiary Family Obligations PKH in Education) - Rahayu, Rizki Budi; Suwitri, Sri (Journal of Public Policy and Management Review, 2019)
There are still The Beneficiary Family Obligations in Education unfulfilling their rights to conform the current regulation become the background of this research. The purpose of this research are to analyze the implementation of the Program Keluarga Harapan in Gambiranom Village Baturetno District Wonogiri Regency and analyze the obstacle factor in the implementation of the Program Keluarga Harapan in Gambiranom Village. The teory which used by the researcher is the implementation theory by Daniel A. Mazmanian and Paul A. Sabatier, also Van Meter and Van Horn with problem characteristic variables and policy environment. The tecniques which uses to collecting the datas are observation, interview, and documentation. The selection of the informants used purposive technique. The results showed that the implementation of the Program Keluarga Harapan in Gambiranom Village was not yet in line with the purpose of creating behavioral changes in Beneficiary Families seen from mentoring activities, commitment verification, and Family Capacity Improvement Meetings that had not been implemented properly so as not to be able to create behavior change. Factor of the implementation are the level of technical difficulties, the level of plurality of the target group, the proportion of the target group to the total population, the scope of expected behavior changes, socio-economic conditions, and support from interest groups. The suggestion that gives by the researcher are the need restricts child association that causes truancy, granting insight to the target group, surveillance and monitoring the childrean and build the sense of resposibility from the The Beneficiary Family Obligations.